1995
DOI: 10.1007/bf00401757
|View full text |Cite
|
Sign up to set email alerts
|

Impaired tyrosine-kinase activity of muscle insulin receptors from hypomagnesaemic rats

Abstract: The effect of magnesium deficiency on glucose disposal, glucose-stimulated insulin secretion and insulin action on skeletal muscle was investigated in rats which were fed a low magnesium-containing diet for 4 days. Control rats were fed a standard diet. Compared to the control rats, the rats fed with low magnesium diet presented: 1) lower serum magnesium levels (0.45 +/- 0.02 vs 0.78 +/- 0.01 mmol/l, p < 0.001), 2) higher basal serum glucose (6.8 +/- 0.02 vs 5.5 +/- 0.2 mmol/l, p < 0.05) and similar basal seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(65 citation statements)
references
References 49 publications
1
58
0
3
Order By: Relevance
“…Meta-analyses of prospective cohort studies and randomized double-blind controlled trials looking at magnesium intake in individuals with type 2 diabetes support decreases in diabetes risk [48], [49], as well as benefits for glycemic control [50]. Magnesium is thought to play a key role in insulin-mediated glucose uptake [51], [52], where animal studies have shown poor intracellular magnesium concentrations to result in defective tyrosine-kinase activity at the insulin-receptor level and therefore impairing insulin action [52], [53]. Similarly, in a meta-analysis of randomized controlled trials looking at the effects of MUFA on glycemic control in individuals with abnormal glucose metabolism, diets high in MUFA were shown to significantly reduce HbA1c [54].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses of prospective cohort studies and randomized double-blind controlled trials looking at magnesium intake in individuals with type 2 diabetes support decreases in diabetes risk [48], [49], as well as benefits for glycemic control [50]. Magnesium is thought to play a key role in insulin-mediated glucose uptake [51], [52], where animal studies have shown poor intracellular magnesium concentrations to result in defective tyrosine-kinase activity at the insulin-receptor level and therefore impairing insulin action [52], [53]. Similarly, in a meta-analysis of randomized controlled trials looking at the effects of MUFA on glycemic control in individuals with abnormal glucose metabolism, diets high in MUFA were shown to significantly reduce HbA1c [54].…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium plays a significant role in glucose and insulin metabolism, mainly through its impact on tyrosine kinase enzyme, magnesium may directly affect Glucose Transporter protein activity 4 and regulate glucose translocation into the cell. [19] …”
Section: Discussionmentioning
confidence: 99%
“…Reduced intracellular magnesium concentrations lead to a decrease in the activity of these enzymes, which, in turn, might favor insulin resistance. It has been shown that insulin resistance in magnesium-deficient rats might be partially attributed to a decrease of tyrosine kinase activity of insulin receptors [117]. At the extracellular level, magnesium moderates intracellular calcium uptake through its nonspecific antagonistic effects on calcium channels [118,119].…”
Section: Magnesium-rich Foodsmentioning
confidence: 99%